Development and utilization of a Process-oriented Information Model for sustainable manufacturing. (October 2015) - Zhang, Heng; Zhu, Bicheng; Li, Yunpeng; Yaman, Omer; Roy, Utpal
Abstract: Nowadays sustainability related decision making plays a critical role in the product design and manufacturing. However, due to the lack of a formal representation of the information regarding the manufacturing processes and sustainability, the sustainability evaluation of the manufacturing processes in the design phase is still inadequate. Thus, a new generation of Computer-Aided Design (CAD) system is needed for the product designers to carry out sustainability related decision makings. The first step toward such a goal is to develop an "information model" to capture and integrate all the relevant information. This paper proposes a Process-oriented Information Model (PIM) to integrate the relevant information regarding the sustainable manufacturing with the product design information. A three-layered framework is also proposed for the utilization of the proposed PIM in a software environment. A case study has been presented to demonstrate a preliminary software system developed based on the proposed PIM and the three-layered framework. It shows the preliminary system has the ability to assist the product designers in making their sustainability related decisions in the product design stage.